1999
DOI: 10.1016/s0022-5347(05)68179-7
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Citrate After Radical Retropubic Prostatectomy

Abstract: Sildenafil improved erectile function and the ability to have intercourse in more than half of men after radical retropubic prostatectomy. Baseline postoperative erectile function, which is dependent on the degree of nerve sparing technique, significantly impacts the likelihood that patients will respond to sildenafil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(38 citation statements)
references
References 17 publications
0
34
0
4
Order By: Relevance
“…Recent small studies reporting the use of sildenafil after radical prostatectomy suggest that response to sildenafil is less impressive than in patients with mixed erectile dysfunction, with the response greater after bilateral nerve-sparing surgery (80 percent) than after unilateral (50 percent) or non-nerve-sparing surgery (0 percent). [8][9][10] Animal studies have shown that bilateral cavernous nerve transection ablates, whereas unilateral nerve sparing preserves, erectile function in the presence of sildenafil. 11 There is a theoretical explanation for this poor response after parasympathetic nerve damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent small studies reporting the use of sildenafil after radical prostatectomy suggest that response to sildenafil is less impressive than in patients with mixed erectile dysfunction, with the response greater after bilateral nerve-sparing surgery (80 percent) than after unilateral (50 percent) or non-nerve-sparing surgery (0 percent). [8][9][10] Animal studies have shown that bilateral cavernous nerve transection ablates, whereas unilateral nerve sparing preserves, erectile function in the presence of sildenafil. 11 There is a theoretical explanation for this poor response after parasympathetic nerve damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The response to sildenafil after radical prostatectomy in which cavernous nerve damage is causal is modest, ranging from 50 to 80 percent. [8][9][10] Animal studies have shown that bilateral cavernous nerve transection ablates erectile function despite the presence of sildenafil. 11 In the absence of a neural signal, sildenafil cannot induce cavernous smooth muscle relaxation and thus an erection.…”
Section: From the Department Of Colorectal Surgery John Radcliffe Homentioning
confidence: 99%
“…B. mit Sildenafil, erfolgversprechend, da dieses Medikament die Erektion verbessern kann [9]. Insbesondere nach unilateraler Nerverhaltung verspricht eine additive Therapie unter den gegebenen Vorsichtsmaßnahmen bei dieser Form der Nerverhaltung einen Gewinn an Lebensqualität für den Patienten.…”
Section: Fragebogengestützte Auswertungenunclassified
“…Ces DE sont accessibles à 70 % des cas à un traitement pharmacologique de relance soit par voie orale soit par voie intracaverneuse [15,16]. Ce traitement pharmacologique peut conduire dans 20 % des cas à une guérison surtout chez les patients jeunes (moins de 60 ans) au statut érectile normal avant l'intervention, et ce d'autant qu'on aura pu leur proposer une intervention avec préservation bilatérale des bandelettes et un traitement des érections administré pré-cocement dans le post-opératoire, voire initialisé dans les semaines pré-opératoires [13,15,28].…”
Section: Après Chirurgie Radicaleunclassified